Soil-structure interaction: A state-of-the-art review of modeling techniques and studies on seismic response of building structures - Bapir, Baban; Abrahamczyk, Lars; Wichtmann, Torsten; Prada-Sarmiento, Luis Felipe (Frontiers in Built Environment, 2023)
The present article aims to provide an overview on the consequences of dynamic soil-structure interaction (SSI) on building structure and the available modeling techniques to deal with SSI problem. The role of SSI has been traditionally considered beneficial on the response of structures; however, recent studies and evidences from past earthquakes showed detrimental effects of SSI in certain conditions, an overview of the related investigations and findings is presented and discussed in this article. Additionally, the main approaches to evaluate seismic soil-structure interaction problem with the commonly used modeling techniques and computational methods are highlighted. The strength, limitations and application cases of each model are also discussed and compared. Moreover, the role of SSI in various design codes and global guidelines are summarized. Finally, the advancements and most recent findings on the SSI effects on seismic response of buildings with different structural system and foundation types are presented. In addition, with the aim of helping new researchers to improve previous findings, the research gaps and future research tendency in the SSI field are pointed out.